2019
DOI: 10.1021/acssuschemeng.9b06599
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Upgrading of Lactic Acid-Based Solvents to Block Copolymer Surfactants

Abstract: We report a new strategy toward the development of block copolymer surfactants from chemicals of the lactic acid family. A particularly unique aspect of this work is the use of green solvents as biobased platform chemicals to generate well-defined and nanostructure-forming materials. Herein, efficient functionalization of ethyl lactate (EL) and N,N-dimethyl lactamide (DML) solvents with acrylate groups generated monomers that could be polymerized by the photoinduced copper-catalyzed living radical polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…3d and e), demonstrating a higher thermal stability than latex dispersions stabilized by conventional chemical surfactants or amphiphilic polymers. 64,65 Ultimately, the stability to electrolyte addition was also proved and no significant changes in particle size or emulsion appearance were observed by saturating the dispersion system with sodium chloride ( Fig. 3d and e).…”
Section: Analysis Of the Latex Dispersionsmentioning
confidence: 78%
“…3d and e), demonstrating a higher thermal stability than latex dispersions stabilized by conventional chemical surfactants or amphiphilic polymers. 64,65 Ultimately, the stability to electrolyte addition was also proved and no significant changes in particle size or emulsion appearance were observed by saturating the dispersion system with sodium chloride ( Fig. 3d and e).…”
Section: Analysis Of the Latex Dispersionsmentioning
confidence: 78%
“…As reported in previous publications, alkyl lactate solvents are appealing chemicals to prepare biorenewable acrylic/methacrylic polymers [23][24][25][26][27][28][29]. Here, BuLA was prepared from L-butyl lactate (BuL) by acylation with acryloyl chloride in the presence of base using a solvent with low environmental impact such as Me-THF (Figure 1).…”
Section: Bula Monomer Synthesis and Raft Polymerization Model Studiesmentioning
confidence: 99%
“…In this regard, our group reported that poly(alkyl lactate ester) (meth)acrylates with controlled molecular weight, narrow molecular weight distribution and high end-group fidelity are also easily accessible by Cu(0) wire-mediated single-electron transfer living radical polymerization (SET-LRP) [27,28]. In a more recent effort, the different water solubility of poly(ethyl lactate acrylate)s (hydrophobic and water-insoluble) and poly(N,N-dimethyl lactamide acrylate) (hydrophilic and water-soluble) was exploited to design amphiphilic AB block copolymers from neoteric lactic acid-based solvents, i.e., ethyl lactate and N,N-dimethyl lactamide, that could self-assemble in aqueous solution to form nanoparticles with different morphologies including large-compound micelles and vesicles [29].…”
Section: Introductionmentioning
confidence: 99%
“…182 Especially biomass-derived solvents such as ethyl lactate already used in the production of polymeric materials could be assessed in the future. 183 Although frequently neglected, another important consideration about these lignin nanomaterials is their biodegradability. While many of the reports focus strictly their attention on the cytotoxicity and biocompatibility studies, the biodegradability of these materials remains largely unexplored.…”
Section: Biomedical Applicationsmentioning
confidence: 99%